Bioenergy for climate change mitigation: Scale and sustainability. Issue 9 (10th July 2021) - Calvin, Katherine; Cowie, Annette; Berndes, Göran; Arneth, Almut; Cherubini, Francesco; Portugal‐Pereira, Joana; Grassi, Giacomo; House, Jo; Johnson, Francis X.; Popp, Alexander; Rounsevell, Mark; Slade, Raphael; et al.
Abstract: Many global climate change mitigation pathways presented in IPCC assessment reports rely heavily on the deployment of bioenergy, often used in conjunction with carbon capture and storage. We review the literature on bioenergy use for climate change mitigation, including studies that use top‐down integrated assessment models or bottom‐up modelling, and studies that do not rely on modelling. We summarize the state of knowledge concerning potential co‐benefits and adverse side effects of bioenergy systems and discuss limitations of modelling studies used to analyse consequences of bioenergy expansion. The implications of bioenergy supply on mitigation and other sustainability criteria are context dependent and influenced by feedstock, management regime, climatic region, scale of deployment and how bioenergy alters energy systems and land use. Depending on previous land use, widespread deployment of monoculture plantations may contribute to mitigation but can cause negative impacts across a range of other sustainability criteria. Strategic integration of new biomass supply systems into existing agriculture and forest landscapes may result in less mitigation but can contribute positively to other sustainability objectives. There is considerable variation in evaluations of how sustainability challenges evolve as the scale of bioenergy deployment increases, due to limitations of existing models, and uncertainty over the future context with respect to the many variables that influence alternative uses of biomass and land. Integrative policies, coordinated institutions and improved governance mechanisms to enhance co‐benefits and minimize adverse side effects can reduce the risks of large‐scale deployment of bioenergy. Further, conservation and efficiency measures for energy, land and biomass can support greater flexibility in achieving climate change mitigation and adaptation. Abstract : We review the literature on bioenergy use for climate change mitigation, including studies that use top‐down integrated assessment models or bottom‐up modelling, and studies that do not rely on modelling. We summarise the state of knowledge concerning potential co‐benefits and adverse side‐effects of bioenergy systems and discuss limitations of modelling studies used to analyse consequences of bioenergy expansion. The implications of bioenergy supply on mitigation and other sustainability criteria are context dependent and influenced by feedstock, management regime, climatic region, scale of deployment and how bioenergy alters energy systems and land use.